Pengaruh Earning Per Share, Price To Book Value, Cash Flow Operating, Stock Return, Dividend Payout Ratio Terhadap Penilaian Ekuitas Perusahaan - Sharen Santoso Rafli; Yanti (Jurnal Ekonomi, 2015)
The purpose of this study is to analyze the effect of Earnings Per Share, Price to Book Value, Cash Flow Operating, Stock Return, Dividend Payout Ratio on the Equity Valuation of companies listed on the Indonesia Stock Exchange. A total sample of 47 manufacturing companies was selected through the purposive sampling method. The results of this study are the earnings per share, dividend payout ratio, and operating cash flow do not have a significant influence on equity valuation. Conversely, the price-to-book value and stock return have a significant influence on equity valuation. Suggestions for future research is to expand the period of research and use other independent variables that have not been tested in this study for example sales, interest rates, retained earnings, stock price, and net income.